Efficacy of CBCT in Detecting Maxillary Sinus Mucosal Thickening and Periapical Pathology in Patients with Odontogenic Anomaly - A Systematic Review and Meta-analysis - Mayurakshi Saha; N. C Sangamesh; S. Bhuvaneshwari; Silpiranjan Mishra; Atul A. Bajoria; Dhirendra K. Singh (Wolters Kluwer Medknow Publications, 2024)
Introduction: Odontogenic infection leads to increased thickness of maxillary sinus membrane. This is aided by close relationship between the roots of upper posterior teeth and floor of the maxillary sinus. This can be viewed by using imaging modalities. Aim: The review has been conducted to compare CBCT (Cone Beam Computed Tomography) with Orthopantomogram (OPG) in detecting maxillary sinus membrane thickening in patients with odontogenic anomaly through a meta-analysis. Materials and Methods: The review was carried out by following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines and was registered as PROSPERO 2023 CRD42023390257. PubMed, Google Scholar and EBSCO host were queried for literature published from January 2000 to December 2022. Newcastle Ottawa scale evaluated the quality of articles. Results: Statistical analysis was performed and forest plot was plotted using RevMan (Review Manager) software version 5.3. Five studies were eligible and two of them were suitable for Meta-Analysis. The Standardized Mean Difference yielded a pooled estimate of 0.39 and preferred CBCT using a random effect model with a P value of 0.02 and an I2 (heterogeneity) value of 59%. Funnel plot showed absence of publication bias. Conclusion: It was concluded that CBCT was effective, as compared to OPG in detecting maxillary sinus membrane thickening with odontogenic anomaly.